Environmental geography and natural hazards : exigencies of appraisal in highland-lowland interactive systems - Pirazizy, A. A. 1960- (New Delhi : Concept Pub. Co., 1992)
Case study of Himachal Pradesh, India.
Includes index.
Includes bibliographical references.
Al Amin
Keywords: Physical geography -- India; Environmental sciences